The focusing of light through 2-D graded photonic crystals - Singh B.K.; Kumar P.; Pandey P.C. (My University, 2025)
We have investigated the strong focusing of electromagnetic waves in novel two-dimensional graded photonic crystals (GPCs). The designed GPCs have the potential to use in optical systems that require compact and powerful focusing elements. © OSA 2014.